Identification of sea urchin sperm adenylate cyclase (The Rockefeller University Press, 1990)
Calmodulin (CaM) affinity chromatography of a detergent extract of sea urchin sperm yielded approximately 20 major proteins. One of these proteins, of Mr 190,000, was purified and used to immunize rabbits. After absorption with living sperm, the serum reacted monospecifically on one- and two-dimensional Western immunoblots with the Mr 190,000 protein. The anti-190-kD serum inhibited 94% of the adenylate cyclase (AC) activity of the CaM eluate. An immunoaffinity column removed 95% of the AC activity, and the purified (but inactive) Mr 190,000 protein was eluted from the column. The antiserum also inhibited 23% of the activity of bovine brain CaM-sensitive AC and 90% of the activity of horse sperm CaM-sensitive AC. These data support the hypothesis that the Mr 190,000 protein is sea urchin sperm AC. Although this AC bound to CaM, it was not possible to demonstrate directly a Ca2+ or CaM sensitivity. However, two CaM antagonists, calmidazolium and chlorpromazine, both inhibited AC activity, and the inhibition was released by added CaM, suggesting the possibility of regulation of this AC by CaM. Indirect immunofluorescence showed the Mr 190,000 protein to be highly concentrated on only the proximal half of the sea urchin sperm flagellum. This asymmetric localization of AC may be important to its function in flagellar motility. This is the first report of the identification of an AC from animal spermatozoa.